Revue für Internationalismus. Bureau der Stiftung für Internationalismus
Dutch ed.: Revue voor internationalisme (ZO 17244). - Engl.ed.: Review of internationalism (ZO 17239). - French ed.: Revue de l'internationalisme (ZO 17242).